1985
DOI: 10.2190/8v89-af7r-urea-degf
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Testing: The Hidden Figures Test

Abstract: The adaptation of paper-and-pencil tests to computers may be confounded by differences between the medium of paper-and-pencil and computers. The purpose of this study was to adapt the Hidden Figures Test for use on PLATO and determine the alternate-form reliability of the computerized version as compared to the paper-and-pencil version. The HFT is one of the most commonly used tests to measure the cognitive style known as field independence-field dependence. The results showed that the test could be adapted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As in previously discussed studies, these kinds of results may have important implications for future equating efforts with computerized tests. In a second HIT study, by Jacobs, Byrd, and High (1985), the test was adapted to be administered by the PLATO system. All the figures and patterns in the computer version were identical in proportion and nearly identical in size to those in the paper-and-pencil version.…”
Section: Tests Containing Graphicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previously discussed studies, these kinds of results may have important implications for future equating efforts with computerized tests. In a second HIT study, by Jacobs, Byrd, and High (1985), the test was adapted to be administered by the PLATO system. All the figures and patterns in the computer version were identical in proportion and nearly identical in size to those in the paper-and-pencil version.…”
Section: Tests Containing Graphicsmentioning
confidence: 99%
“…A second study using similar tests (Kiely, Zara, and Weiss 1986) found no mode-ofadministration main effects; however, a significant test mode by order interaction was observed for two of the three tests in the study. Two studies (Jacobs, Byrd, and High 1985;Jonassen 1986) found computer versions of theHl-T more difficult than were paper-and-pencil versions. However, only in the latter study were the differences statistically significant.…”
Section: Tests Containing Graphicsmentioning
confidence: 99%
“…Although one study (Lee, Moreno, & Sympson, 1986) found a significantly lower mean score with a CBT than with a PPT, several other studies have found differences between the test modes to be nonsignificant (Jacobs, Byrd, & High, 1985;D. F. Johnson & Mihal, 1973;Olsen et al, 1986;Wise & Wise, 1987).…”
mentioning
confidence: 92%
“…Three of the studies found no evidence for significant differences caused by mode of administration (Reckase, Carlson, & Ackerman, 1986;Kiely, Zara, & Weiss, 1986;Jacobs, Byrd, & High, 1985) while the other two studies did (Wilgrube, 1982;Jonassen, 1986) The amount of experience with computers is also a significant factor in computer anxiety because anxiety is produced in part, by a lack of familiarity with computer use. In fact, a major finding of the study by Levin and Gordan (1989) suggested that prior computer exposure has a stronger influence on attitudes than does gender.…”
Section: An Obvious Difference Between Paper-and-mentioning
confidence: 99%